A Convenient Synthetic Route of Diethyl (4‐Oxo‐chromeno[2, 3‐d]pyrimidin‐2(5)‐yl)phosphonates. (28th March 2019) - Ali, Tarik E.; Assiri, Mohammed A.; Hassanin, Noha M.; Yahia, I. S.; Hussien, Mai S. A.
Abstract : Novel diethyl (4‐oxo‐3, 4‐dihydro‐2 H ‐chromeno[2, 3‐ d ]pyrimidin‐2‐yl)phosphonate as two enantiomers and diethyl (4‐oxo‐1, 5‐dihydro‐4 H ‐chromeno[2, 3‐ d ]pyrimidin‐5‐yl) phosphonate were obtained in easy procedure via reaction of 2‐imino‐2 H ‐chromene‐3‐carboxamide, dimethylformamide dimethyl‐acetal, and diethyl phosphite in a simple one pot. Possible reaction mechanisms were proposed. The structures of the obtained products were confirmed by elemental analyses and spectral tools. Abstract :